Effect of Polymer on the Properties of Bitumen and Pavement Layers, Case Study: Expressway No.1, Republic of Iraq. Issue 1 (March 2021) - Badry, Mohamed MM.; Dulaimi, Anmar; Shanbara, Hayder Kamil; Al-Busaltan, Shakir; Abdel-Wahed, Talaat
Abstract: Increasing attention has been paid to use polymer as a modifier in bituminous mixtures manufacturing. Unmodified bituminous mixtures are highly affected by the undesirable environmental conditions at which such mixtures present brittle behaviour and crack at cold weather, whereas present soft behaviour at elevated temperatures resulting in rutting and surface deformation. As a result of bituminous mixtures modification using polymers, more elastic and durable bituminous materials that show developed stability at high temperatures can be obtained. In this present study, using 4% polymer with bitumen grade of 40/50 leads to improve bitumen properties such as viscosity, penetration, flash point, softening point, dynamic shear and creep stiffness. The results of investigation samples which were cutting from pavement show improvement of these pavement properties according to results of tests at site lab and independent lab. The use of polymer in design mixture of asphalt help in improving pavement properties which lead to the successful road and increases the age of pavements and become more resistant to hard conditions such as high temperature in the middle east region.